Generalized height-diamanter and crown diameter prediction models for cork oak forest in Spain - Sanchez Gonzalez, M.=700 1 Cañellas, I.; Montero, G.
(En, Es)
Ilus., 59 ref.
Keywords: QUERCUS SUBER; MODELOS; DIAMETRO; CUBIERTA DE COPAS; ESPAÑA; MODELIZACION FORESTAL; RELACION ALTURA-DIAMETRO; DIAMETRO DE COPA; MODELOS MIXTOS